Investigating the Factors that Impact the Selection of Technical Ingredients in Food Manufacturing: A Mixed-Methods Study. Issue 3 (4th May 2021) - Traynor, Mark; Martin, David S.; Ahmad, Imran; Alonso, Miguel
ABSTRACT: This paper explores the factors that influence the selection and application of technical ingredients by food and beverage manufacturers. A mixed-method design was used to collect both qualitative and quantitative data from 54 US-based food and beverage manufacturers. Thematic analysis of the quantitative data identified several themes and subthemes. Technical properties (88.09) and clean label (78.79) were found to be important factors. However, results indicated that clean label items are growing in importance and that such items may be selected even when more functionally appropriate ingredients already exist. The quantitative results of the study supported these findings, but there is appears to be a break-even point where clean label items cannot replace certain ingredients due to the technical requirements of the final product. This research adds to the limited literature regarding how consumer perceptions and trends impact the selection and application of technical ingredients.